Diagnostic and therapeutic guidelines in thoracic surgery. Anesthesia in thoracopulmonary surgery: coordinador Alfredo Ruiz Liard - Salsamendi, María Julia; Quiroz, Darío; Cassinelli, Nilda (Cirugía del Uruguay, 1975)
Contains Bronchoscopy and thoracic surgery / Eduardo Casamayou Respiratory functionality and lung surgery / Ariel Quereilhac Behavior in the face of complicated pulmonary hydatidosis / Jorge Nin Vivó Treatment guidelines for hepatothoracic hydratic transit / Hamlet Suárez Conduct against spontaneous pneumothorax / José L Martínez Apezteguía Treatment guidelines for pleural empyemas / Jorge Nin Vivó and Horacio Etchemendy Our position on bronchiectasis / Alfredo Ruiz Liard and Mario Brandolino A surgical solution for dyspnea in diffuse pulmonary emphysema. Lung remodeling / Valentín L Crosa Dorado